Effect of Second Generation Antipsychotics on Caregiver Burden in Alzheimer Disease - Mohamed, Somaia (2011)
CONTEXT: Alzheimer disease (AD) imposes a severe burden upon patients and their caregivers. Severity of psychiatric symptoms and behavioral disturbances are important determinants of caregivers’ experience of burden. These symptoms may be improved with atypical antipsychotic treatment. OBJECTIVE: In this study we use data from the CATIE-AD trial to evaluate the effect of atypical antipsychotics as compared to placebo on the experiences of caregivers of outpatients with Alzheimer disease. DESIGN: We compared the effect of atypical antipsychotic drugs (olanzapine, risperidone or quetiapine) considered together as a group, to placebo, on experiences of caregivers of AD outpatients. We also evaluated whether improvement in patients’ psychiatric and behavioral symptoms mediated the relationship between drug treatment and caregiver burden. SETTING: CATIE-AD included outpatients in usual care settings, and assessed treatment effectiveness over a nine-month period. PARTICIPANTS: Data from CATIE-AD participants who had at least one post-baseline outcome assessment, and from their caregivers, were examined in an intention-to-treat analysis (ITT) (N=361), and then in a phase 1 only analysis including only observations while on the initially randomized drug (N=153). MEASURES: The Burden Interview, Beck Depression Inventory, and the NPI Caregiver Distress Scale were used to evaluate caregiver burden. RESULTS: In both ITT and phase 1-only analyses, caregivers of patients treated with second generation antipsychotics (SGAs) scored significantly lower than those on placebo on both the Burden Interview (p = 0.009) and the NPI Caregiver Distress Scale’s scores (p = 0.0209). These differences appeared to have been mediated by lower levels of agitation, hostility, and psychotic distortions. CONCLUSION: In AD patients with symptoms of psychosis, agitation or aggressive behavior, medications can have a small but significant impact on caregiver burden.